Pelatihan Pembuatan Media Pembelajaran dengan Menggunakan Scratch - Emma Martina Pakpahan; Christin Erniati Panjaitan; Yuda Raviansah Silalahi (Jurnal Pengabdian Masyarakat Nusantara, 2026)
The high demands on the use of technology impact the use of digital teaching media in the learning process. In reality, many teachers still have difficulty using technology as teaching media. This community service activity aims to help teachers create innovative technology-based learning media. This activity was carried out at SMAS in Tebing Tinggi. In this activity, teachers took part in training which was carried out for 2 days offline. Teachers are taught how to create learning media using scratch. This training was attended by 12 teachers from various fields of study. The participants were given a pre-test and post-test regarding the use of scratch. Pre-tests and post-tests were given to determine the teacher's level of understanding regarding the use of scratch. The test results showed that 75% of participants were interested in creating learning media using scratch and using it in class. Participants also admitted that teaching media using scratch is easy to understand and can be easily accessed and used.